Internal Maxillary Artery-Radial Artery-Middle Cerebral Artery Bypass and STA-MCA Bypass for the Treatment of Complex Middle Cerebral Artery Bifurcation Aneurysm: A Case Report - Huang, Chaojue; Qin, Shixing; Cao, Guan; Huang, Wei; Yu, Yongjia (Frontiers in Surgery, 2022)
Background: Children's complex middle cerebral artery（MCA）aneurysm is relatively rare. When the huge aneurysm is located in the MCA bifurcation with inconspicuous neck and involving numerous arteries, intravascular interventional surgery or aneurysm clipping is often difficult to treat. At this point, high flow bypass revascularization is necessary as a treatment to preserve cerebral blood flow. In recent years, the internal maxillary artery (IMA) has gradually become the mainstream donor artery of high flow bypass, we performed internal maxillary artery -radial artery-middle cerebral artery（IMA-RA-MCA）+ superficial temporal artery-middle cerebral artery（STA-MCA） bypass as the treatment of a complex MCA bifurcation aneurysm in consideration of the patient's condition and the advantage of the IMA. According to the author, this case is the youngest reported case of IMA-RA-MCA bypass at present. Case Description: An male child, 7 years and 8 months, was admitted to the hospital due to "recurrent headache for more than 9 months", DSA indicated that there was a large wide-necked aneurysm at the bifurcation of the right MCA M1 segment, with a size of about 1.16*1.58*1.32cm. The aneurysm’s inflow path was in front of M1 bifurcation, and one outflow path originate from the aneurysm body, and another small outflow path attached to the aneurysm body. After completing the preoperative evaluation, an extended pterional approach with zygomatic osteotomy was performed to fully exposed the aneurysm and IMA, harvesting the left radial artery at the same time, then performed STA-MCA bypass, IMA-RA-MCA bypass and aneurysm trapping. postoperative re-examination showed that bypass vessels and the distal middle artery vessels were patency and the aneurysm disappeared, the child has no neurological dysfunction. Conclusions: IMA-RA-MCA bypass is an effective high-flow cerebral blood reconstruct scheme in the treatment of complex middle cerebral artery bifurcation aneurysms. This case can provide a reference for the surgical treatment of complex middle cerebral artery bifurcation aneurysms in children.